(untitled) (Lex Scientia Law Review, 2024)
The pattern of resolving disputes in regional head elections still adheres to a centralistic system or is carried out by institutions at the central level even though regional head elections are a regime of regional government not central government. This study aims to outline the urgency and challenges of decentralizing dispute resolution of regional elections. At the same time, an ideal design form for election dispute resolution with a decentralized model is also offered ranging from relief, competence to procedural law. This research uses a normative type of research with an approach to the provisions of laws and regulations, concepts, and cases. The centralization of electoral dispute resolution has implications for regime misalignment, making for a corrupt judicial process and requiring high accommodation costs. The antithesis to the centralization model of dispute resolution is through decentralization, which is an election dispute resolution that is tried at the regional level according to the location of the election so that there is a harmony of the regime model between the dispute resolution regime and the electoral regime. The decentralization model starts from the judicial institutions that stand at the regional level, their absolute and relative competence and procedural law starting from subjectum letis, objectum letis and verdicts.